Internalizing the Code of Journalistic Ethics from an Islamic Perspective for Beginner Journalists - Lubis, Kholilah; Simbolon, Nurmayanti Fitri; Amalia, Riadhoh; Nasution, Sahara Nurfitri; Rahmadani, Fadhilah; Amanda, Agnes; Alawi, Muhammad; Da'i, Raja Ali (PT Agung Media Publisher, 2025)
The adherence to journalistic ethics is crucial for ensuring responsible and professional journalism. However, understanding and applying these ethics, especially from an Islamic perspective, presents challenges for beginner journalists. This study aims to explore the internalization of Islamic journalistic ethics among beginner journalists and identify the strategies to strengthen their ethical practices. The study employs a qualitative approach using Participatory Action Research (PAR), involving beginner journalists in interactive discussions and real-life case studies to facilitate the understanding and application of Islamic journalistic ethics. Data was collected through interviews and group discussions with journalists at various media outlets. The findings reveal that while beginner journalists have a basic understanding of journalistic ethics, their knowledge of Islamic principles, such as honesty, trustworthiness, and justice, is limited. The challenges in implementing these principles are primarily influenced by industry pressures, organizational culture, and the tension between press freedom and moral responsibility. The study highlights the need for deeper education and training on Islamic journalistic ethics to enable journalists to consistently apply these principles in their daily work. It emphasizes the importance of creating supportive environments for ethical behavior and fostering collaboration between media, educational institutions, and religious organizations. Future research should explore the broader application of Islamic ethics in digital media and investigate technological solutions to enhance ethical practices in journalism.